Improvement of soft soil by using fly ash and bottom ash as soil stabilizer - Mohd Azfar Irfan, Md Nasir (2013)
The studies conducted is focused on stabilization of soil situated in Pekan area which are chosen to be the investigation areas. The uses of fly ash and bottom ash in soil stabilization are intended to improve the physical properties of soil structural engineering. The amount of fly ash and bottom ash tried were 5%, 10%, 15%, 20%, and 25% by weight. Each testing was conducted five times to get the average value. The specimens were determined by using the laboratory testing such as particle size analysis, atterberg limits, standard proctor test, falling head permeability test, and unconfined compression test. According to AASHTO, the soil is classified by referred to the passing sieve No. 10, No. 40, and No. 200 which are 75.54%, 66.43% and 55.76% respectively. The average moisture content of plastic limit for the control soil is 36.71%. When cone penetration is 20mm, the moisture content of the soil is* 38.5% for liquid limit. From this data, the plasticity index of the soil is 1.79%. From the giaph compaction curve of control soil, it shows that the maximum dry density is 17.22 kN/m 3 and the optimum moisture content is 13.0%. The control soil has the lowest averages ofthepermeability coefficient which is 2.12 is 1.132 X 10'° kN/m2. From Mohr's circle, the cohesion value that obtained is 0.566 x 10'° kNim 2. The consistency of control soil can categorize as very soft clay where the q value are in range 0 kN/m 2 to 24 kN/m 2 . By comparing the liquid limit, plastic index and x 10-4 cm/s. The value of unconfined compressive strength, qu optimum water content for both fly ash and bottom ash, the additional of 25% bottom ash gave the lowest values than others percentages which mean that the soil were have the highest of maximum dry density. By comparing the values of unconfined compressive strength for both fly ash and bottom ash, the additional of 25% bottom ash give the highest value of compressive strength which is 1.465 x 10'0 kN/m2 and 0.732 x 10.10 kN/m2 for the cohesion value than others percentages.